The Role of PT Danamas Insan Kreasi Andalan in Enhancing Community Economic Development: An Islamic Economic Perspective (Cirebon Branch) - Siti Hartina; Gama Pratama; Ahmad Munajim; Mohammad Ridwan (Prodi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam Universitas Islam Bunga Bangsa Cirebon, 2026)
This study aims to examine the role of PT Danamas Insan Kreasi Andalan in enhancing community economic development from an Islamic economic perspective, with a focus on the Cirebon branch. The research adopts a qualitative approach through observations, interviews, and document analysis to explore the company’s contributions to local economic empowerment. The findings indicate that PT Danamas Insan Kreasi Andalan plays a significant role in improving community welfare by providing accessible financial services and supporting small-scale businesses. From the perspective of Islamic economics, the company’s practices reflect fundamental principles such as justice, mutual benefit, and social responsibility. These values contribute to the creation of inclusive and sustainable economic growth within the community. However, the study also highlights the need for continuous improvement in service quality and outreach to maximize its impact. Overall, the company demonstrates strong potential in fostering community economic development aligned with Islamic economic principles.